Three Centuries of Conflict in East Timor - Kammen, Douglas Anton (NUS Press, 2016)
Why does violence recur in some places, over long periods of time? Douglas Kammen explores this pattern in Three Centuries of Conflict in East Timor, studying that island's tragic past. The questions posed in the book about recurring violence and local narratives apply to many other places besides East Timor